2008
DOI: 10.1073/pnas.0802726105
|View full text |Cite
|
Sign up to set email alerts
|

A NOD2–NALP1 complex mediates caspase-1-dependent IL-1β secretion in response to Bacillus anthracis infection and muramyl dipeptide

Abstract: NOD2, a NOD-like receptor (NLR), is an intracellular sensor of bacterial muramyl dipeptide (MDP) that was suggested to promote secretion of the proinflammatory cytokine IL-1␤. Yet, the molecular mechanism by which NOD2 can stimulate IL-1␤ secretion, and its biological significance were heretofore unknown. We found that NOD2 through its N-terminal caspase recruitment domain directly binds and activates caspase-1 to trigger IL-1␤ processing and secretion in MDP-stimulated macrophages, whereas the C-terminal leuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
306
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(325 citation statements)
references
References 40 publications
(60 reference statements)
13
306
2
4
Order By: Relevance
“…In contrast, it appears that in unstimulated macrophages NLRP1 components are not preassembled in a multiprotein complex, but rapidly form protein-protein associations upon stimulation by muramyl dipeptide. 13 In this regard, immunoprecipitation experiments indicate protein-protein interactions are made between NLRP1, ASC, caspase-1, caspase-11, and XIAP in neuronal lysates of sham and spinal cord-injured and brain-injured rodents. 5,6 These studies indicate that the inflammasome components in the CNS are preassembled before activation; however, it is possible that additional inflammasome proteins are recruited into inflammasome complexes as the inflammatory response becomes exacerbated.…”
Section: The Nlrp1 Inflammasomementioning
confidence: 99%
“…In contrast, it appears that in unstimulated macrophages NLRP1 components are not preassembled in a multiprotein complex, but rapidly form protein-protein associations upon stimulation by muramyl dipeptide. 13 In this regard, immunoprecipitation experiments indicate protein-protein interactions are made between NLRP1, ASC, caspase-1, caspase-11, and XIAP in neuronal lysates of sham and spinal cord-injured and brain-injured rodents. 5,6 These studies indicate that the inflammasome components in the CNS are preassembled before activation; however, it is possible that additional inflammasome proteins are recruited into inflammasome complexes as the inflammatory response becomes exacerbated.…”
Section: The Nlrp1 Inflammasomementioning
confidence: 99%
“…25,26 NLRP1 can also associate with NOD2 to mediate caspase-1-dependent IL-1b secretion in response to Bacillus anthracis and MDP. 27,28 Recently a fourth type of inflammasome has been identified, involving the protein absent in melanoma 2 (AIM2) (Figure 1). 29 Despite the lack of NACHT domain, AIM2 can undergo oligodimerization and recruit ASC via PYD in response to double stranded cytosolic DNA through its C-terminal HIN domain.…”
Section: The Inflammasomesmentioning
confidence: 99%
“…13 Activation of NLRP1 is triggered by (muramyl dipeptide) and the lethal Bacillus anthracis toxin. [14][15][16][17] A unique feature of NLRP1 is that it can localize in the nucleus unlike other inflammasomes which are distributed in the cytoplasm. 18 …”
Section: Nlrp1 Inflammasomementioning
confidence: 99%
“…53 Hsu et al showed that the formation of NLRP1 inflammasome was ASC-dependent in humans whereas mouse NLRP1b caused the activation of caspase-1 in an ASC-independent manner. 17 Indeed, muramyl dipeptide can be sensed by NLRP1, like NOD2 and NLRP3. 54 Microbial infection elicits effector mechanisms during the process of host defense.…”
Section: Inflammasomes Initiate Antimicrobial Host Responsementioning
confidence: 99%